ANALYSIS THE IMPACT FACTORS OF APPLICATION CONSERVATION FARMING ON PRODUCTIVITY POTATO FARMING IN BUMIAJI BATU INDONESIA - Novil Dedy Andriatmoko; Nuhfil Hanani; Syafrial Syafrial; Peng Ke-Chung (Socio-Economics/Agribusiness Department, 2018)
This paper attempts to find out the potato conservation farming in Batu, East Java, Indonesia. This research is conducted because the potato can be used to substitute rice. Data used in this study is primary data obtained from the research location, Bumiaji, Batu, Indonesia. This study has three objectives. First objective is to find out the impact of conservation on farmers’ income; the second is to assess the adoption rate of conservation farming; and the third is farming efficiency of the potato farming, as well as the adoption of conservation farming implementation factors. From the research results, the implementation of conservation influences the income of farmers. From second objective, it can be found that the efficiency level of potato production is relatively low. Additionally, the factors that influence farmers to adopt conservation farming are age, land area, and knowledge of the importance of conservation farming.